The Use of Operational Excellence Principles in a University Hospital - Edelman, Eric R.; Hamaekers, Ankie E. W.; Buhre, Wolfgang F.; van Merode, Godefridus G. (Frontiers in Medicine, 2017)
Abstract The introduction of Operational Excellence in the Maastricht University Medical Center (MUMC+) has been the first of its kind and scale for a university hospital. The policy makers of the MUMC+ have combined different elements from various other business, management and healthcare philosophies and frameworks into a unique mix. This paper summarizes the journey of developing this system and its most important aspects. Special attention is paid to the role of the operating rooms and the improvements that have taken place there, because of their central role in the working of the hospital. The MUMC+ is the leading tertiary healthcare center for the South-East region of The Netherlands and beyond. Regional, national and international developments encouraged the MUMC+ to start significantly reorganizing its care processes from 2009 onwards. First experiments with Lean Six Sigma and Business Modeling were combined with lessons learned from other centers around the world to form the MUMC+’s own type of Operational Excellence. At the time of writing, many improvement projects of different types have been successfully completed. Every single department in the hospital now uses Operational Excellence and design thinking in general as a method to develop new models of care. An evaluation in 2014 revealed several opportunities for improvement. A large number of projects were in progress, but 75% of all projects had not been completed, despite the first projects being initiated back in 2012. This led to a number of policy changes, mainly focusing on more intensive monitoring of projects and trying to do more improvement projects directly under the responsibility of the line manager. Focusing on patient value, continuous improvement and the reduction of waste have proven to be very fitting principles for healthcare in general and specifically for application in a university hospital. Approaching improvement at a systems level while directly involving the people on the work floor in observing opportunities for improvement and realizing these has shown itself to be essential.